PENGARUH ION KROMIUM(III) PADA EKSTRAKSI ION TEMBAGA(II) MENGGUNAKAN EMULSI KEROSEN DENGAN 1-FENIL-3-METIL-4-BENZOIL-5-PIRAZOLON SEBAGAI PEMBAWA KATION - Hamzah, Baharuddin; Said, Irwan; Hardani, Ririen (Jurnal Akademika Kimia, 2013)
The influence of chromium(III) ion on copper(II) ion extraction using kerosene emulsion with 1-phenyl-3-methyl-4-benzoyl-5-pyrazolone (HPMBP) as a cation carrier was investigated. The optimum condition for copper(II) extraction were as follows: concentration of mixed surfactant (span 80+span 20) was 5%, volume ratio of kerosene and internal phase was 1, concentration of HPMBP was 0.025 M, concentration of HCl was 1 M, volume ratio of emulsion and external phase was 0.143. The results showed that the extraction of copper(II) ion was selective to chromium(III) ion, relatively. The result also showed that the presence of 500 ppm chromium(III) ion decrease the percentage of copper(II) ion extraction from 98.6 to 91.0.